Lexical-perceptual integration influences sensorimotor adaptation in speech - Bourguignon, Nicolas J.; Baum, Shari R.; Shiller, Douglas M. (Frontiers in Human Neuroscience, 2014)
A combination of lexical bias and altered auditory feedback was used to investigate the influence of higher-order linguistic knowledge on the perceptual aspects of speech motor control. Subjects produced monosyllabic real words or pseudo-words containing the vowel [ε] (as in "head") under conditions of altered auditory feedback involving a decrease in vowel first formant (F1) frequency. This manipulation had the effect of making the vowel sound more similar to [I] (as in "hid"), affecting the lexical status of produced words in two Lexical-Change (LC) groups (either changing them from real words to pseudo-words: e.g., less – liss, or pseudo-words to real words: e.g., kess – kiss). Two No-Lexical-Change (NLC) control groups underwent the same auditory feedback manipulation during the production of [ε] real- or pseudo-words, only without any resulting change in lexical status (real words to real words: e.g., mess – miss, or pseudo-words to pseudo-words: e.g., ness – niss). The results from the LC groups indicate that auditory-feedback-based speech motor learning is sensitive to the lexical status of the stimuli being produced, in that speakers tend to keep their acoustic speech outcomes within the auditory-perceptual space corresponding to the task-related side of the word/non-word boundary (real words or pseudo-words). For the NLC groups, however, no such effect of lexical status is observed.